1999
DOI: 10.1161/01.res.85.10.892
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Epithelial Growth Factor Receptor Pathway by Unsaturated Fatty Acids

Abstract: Abstract-Nonesterified fatty acids (NEFAs) are acutely liberated during lipolysis and are chronically elevated in pathological conditions, such as insulin resistance, hypertension, and obesity, which are known risk factors for atherosclerosis. The purpose of this study was to investigate the effect and mechanism of action of NEFAs on the epithelial growth factor (EGF) receptor (EGFR). In the ECV-304 endothelial cell line, unsaturated fatty acids triggered a time-and dose-dependent tyrosine phosphorylation of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 48 publications
1
52
0
5
Order By: Relevance
“…This conflicts with perceived thinking about olive oil, previously thought to be a major dietary component responsible for reducing the risk of clinically significant CaP in Mediterranean men (Simopoulos, 2004;Stamatiou et al, 2007). Oleic acid has been shown to activate EGFR signalling in both endothelial (Vacaresse et al, 1999) and breast cancer cell lines (Soto-Guzman et al, 2008). Angelucci et al (2008) has previously reported that AA stimulates the EGFR pathway leading to increased cellular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This conflicts with perceived thinking about olive oil, previously thought to be a major dietary component responsible for reducing the risk of clinically significant CaP in Mediterranean men (Simopoulos, 2004;Stamatiou et al, 2007). Oleic acid has been shown to activate EGFR signalling in both endothelial (Vacaresse et al, 1999) and breast cancer cell lines (Soto-Guzman et al, 2008). Angelucci et al (2008) has previously reported that AA stimulates the EGFR pathway leading to increased cellular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Au niveau cellulaire, les acides gras sont utilisés pour le renouvellement des membranes ou comme source d'énergie via la b-oxydation qui a lieu dans la mitochondrie. Les acides gras activent diverses voies de signalisation (PKC, MAPK) [20] ainsi que l'EGF récepteur (EGFR) via une modification de la fluidité membranaire, cet effet étant directement lié au degré d'insaturation des acides gras [21]. Les acides gras ont de multiples interactions avec la mitochondrie, et peuvent moduler les ROS mitochondriaux soit directement par la b-oxydation (qui active la chaîne respiratoire), soit via un effet décou-plant.…”
Section: Acides Gras Ros Et Pathologies Vasculairesunclassified
“…Les acides gras activent de nombreuses voies de signalisation, telles que la PKC, les MAP kinases, la PI3 kinase et l'EGFR [20,21]. La phosphorylation et l'activation de l'EGFR par les acides gras est due (en partie) à une modification de la fluidité membranaire [21].…”
Section: L'activation De La Gpx Par L'acide Oléique Dépend De L'egf Runclassified
See 2 more Smart Citations